2019
DOI: 10.1186/s12864-019-6074-6
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering sperm metabolome to discover biomarkers for bull fertility

Abstract: Background Subfertility decreases the efficiency of the cattle industry because artificial insemination employs spermatozoa from a single bull to inseminate thousands of cows. Variation in bull fertility has been demonstrated even among those animals exhibiting normal sperm numbers, motility, and morphology. Despite advances in research, molecular and cellular mechanisms underlying the causes of low fertility in some bulls have not been fully elucidated. In this study, we investigated the metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
2
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 110 publications
(153 reference statements)
0
58
2
3
Order By: Relevance
“…In this regard, the study of SP components is gaining interest. In both men [32,33,[36][37][38][39] and bulls [40][41][42], SP metabolites have been linked to sperm function, pointing at a possible role as markers of sperm quality and/or fertility. These studies evidence that an in-depth metabolomic profile of SP could provide a valuable list of potential sperm quality and fertility biomarkers for AI-boars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the study of SP components is gaining interest. In both men [32,33,[36][37][38][39] and bulls [40][41][42], SP metabolites have been linked to sperm function, pointing at a possible role as markers of sperm quality and/or fertility. These studies evidence that an in-depth metabolomic profile of SP could provide a valuable list of potential sperm quality and fertility biomarkers for AI-boars.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between SP metabolites and sperm functionality have also been reported in humans, showing that the contribution of metabolites such as uric acid, tryptophan or taurine, maintains reactive oxidative species (ROS) at low levels in this specie [ 35 ]. In addition, the relationship between SP metabolites and fertility has been evidenced in both humans [ 32 , 33 , 36 , 37 , 38 , 39 ] and cattle [ 40 , 41 ], with several metabolites that can explain male infertility in humans [ 32 , 33 , 36 , 37 , 38 , 39 ] or can potentially serve as biomarkers of bull fertility [ 40 , 41 , 42 ]. To the best of our knowledge, however, there is no information regarding the metabolomic profile of pig SP.…”
Section: Introductionmentioning
confidence: 99%
“…Saturated fatty acids, especially the long-chained SFA such as 22:0, modify the fluidity of cellular membrane by increasing the energy (higher melting point) required for maintaining fluidity. In addition, it has been reported that MUFA was inversely related to post-thaw sperm viability in human sperm and these reports suggested that oleic acid may be a substrate of lipid oxidation 19,40 , which might cause a decrease in sperm motility 24,26 . However, in the current study, 18:1 cis9 (oleic acid) was more abundant in the PL fraction of Good freezability sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine, formed by the hydrolysis of phosphatidylcholine, a normal component of sperm plasma membrane, influences motility, capacitation and acrosome reaction [27,28], contributing to membrane-fusion events during fertilization [68]. In a previous study, other metabolites, such as gamma-aminobutyric acid, carbamate, benzoic acid, lactic acid and palmitic acid, were identified as potential bull fertility markers, but a different method of analysis (i.e., GS-MS) was employed [20].…”
Section: Metabolomic Analysis Of Spermatozoa From Hf and Lf Bullsmentioning
confidence: 99%
“…This approach allows for the comprehensive identification of metabolites, such as amino acids, peptides, fatty acids and carbohydrates in secretions, cells, tissues and organs [17][18][19]. Metabolomics has been recently used to identify male fertility biomarkers in farm animals, including cattle [20,21]. Seminal plasma has long been used as a key source to investigate male infertility.…”
Section: Introductionmentioning
confidence: 99%